Marital status is a prognostic factor in amyotrophic lateral sclerosis. (3rd May 2017) - Spataro, R.; Volanti, P.; Lo Coco, D.; La Bella, V.
Abstract : Background and objectives: Several variables have been linked to a shorter survival in patients with amyotrophic lateral sclerosis (ALS), for example, female sex, older age, site of disease onset, rapid disease progression, and a relatively short diagnostic delay. With regard to marital status, previous studies suggested that living with a partner might be associated to a longer survival and a higher likelihood to proceed to tracheostomy. Therefore, to further strengthen this hypothesis, we investigated the role of marital status as a prognostic variable in a cohort of ALS patients. Methods: We performed a retrospective analysis on 501 consecutive ALS patients for which a complete disease's natural history and clinical/demographic data were available. At diagnosis, 409 patients (81.6%) were married or lived with a stable partner, whereas 92 patients (18.4%) were single/widowed/divorced. Results: In our ALS cohort, being married was associated with a median longer survival (married, 35 months [24‐50] vs unmarried, 27 months [18‐42]; P <.004). Moreover, married and unmarried patients were significantly different in many clinical and demographic variables, including age at disease onset, gender, body mass index, and number of children. Cox regression analysis showed that age at onset, diagnostic delay, and marital status were independent predictors of survival. In unmarried patients, female sex was also significantly associated with shorter survival. Conclusions: Marital status is a prognostic factor in ALS, and it significantly affects survival.